A Practical Comparison of Waqf (Islamic Endowment) in Indonesia and Other Countries - Sulistiawati, Nila; Rini, Rini; Nadratuzzaman, Muh.; Amalia, Euis (CV. Publikasi Indonesia, 2023)
The definition of waqf in one of the results of this study is